2020
DOI: 10.3389/fphys.2020.00421
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Vessel Permeability by TRP Channels

Abstract: The vascular endothelium constitutes a semi-permeable barrier between blood and interstitial fluids. Since an augmented endothelial permeability is often associated to pathological states, understanding the molecular basis for its regulation is a crucial biomedical and clinical challenge. This review focuses on the processes controlling paracellular permeability that is the permeation of fluids between adjacent endothelial cells (ECs). Cytosolic calcium changes are often detected as early events preceding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 100 publications
(136 reference statements)
0
9
1
Order By: Relevance
“…TRP channels provide an alternative pathway for extracellular Ca 2+ entry in both vascular endothelial cells ( Negri et al, 2020a ) and ECFCs ( Inoue and Xiong, 2009 ; Hofmann et al, 2014 ; Dragoni et al, 2015a ; Figure 1 ). Endothelial cells use TRP channels to sense the local microenvironment in which they reside, thereby adapting to subtle changes in the chemical composition of the extracellular milieu and/or in the mechanical forces acting on the vascular wall ( Genova et al, 2020 ; Negri et al, 2020a ). For instance, the endothelial TRPV1 is sensitive to an increase in local temperature above 43°C ( Negri et al, 2020b ) and/or in local hydrogen peroxide (H 2 O 2 ; DelloStritto et al, 2016 ), whereas TRPV4 is sensitive to physical stimuli, such as shear stress ( Schierling et al, 2011 ) and pulsatile stretch ( Thodeti et al, 2009 ), and to arachidonic acid (AA) production ( Fiorio Pla et al, 2008 ).…”
Section: Intracellular Ca 2+ Signaling Drives Ecfcmentioning
confidence: 99%
See 1 more Smart Citation
“…TRP channels provide an alternative pathway for extracellular Ca 2+ entry in both vascular endothelial cells ( Negri et al, 2020a ) and ECFCs ( Inoue and Xiong, 2009 ; Hofmann et al, 2014 ; Dragoni et al, 2015a ; Figure 1 ). Endothelial cells use TRP channels to sense the local microenvironment in which they reside, thereby adapting to subtle changes in the chemical composition of the extracellular milieu and/or in the mechanical forces acting on the vascular wall ( Genova et al, 2020 ; Negri et al, 2020a ). For instance, the endothelial TRPV1 is sensitive to an increase in local temperature above 43°C ( Negri et al, 2020b ) and/or in local hydrogen peroxide (H 2 O 2 ; DelloStritto et al, 2016 ), whereas TRPV4 is sensitive to physical stimuli, such as shear stress ( Schierling et al, 2011 ) and pulsatile stretch ( Thodeti et al, 2009 ), and to arachidonic acid (AA) production ( Fiorio Pla et al, 2008 ).…”
Section: Intracellular Ca 2+ Signaling Drives Ecfcmentioning
confidence: 99%
“…It has, therefore, been suggested that targeting TRP channels could represent an efficient strategy to boost ECFCs' regenerative potential (Moccia et al, 2015(Moccia et al, , 2018a. Indeed, TRP channels are physically coupled to specific Ca 2+ -dependent effectors which translate extracellular Ca 2+ entry through specific pathways into precise biological outputs which differentially affect endothelial cell fate (Smani et al, 2018;Genova et al, 2020;Negri et al, 2020a). ) and chemokines (like SDF-1) bind to Receptor tyrosine kinases (RTKs) and G protein-coupled receptors (GPCRs) respectively, thus activating specific PLC isoforms, which in turn leads to production of inositol 1,4,5-trisphosphate (InsP 3 ).…”
Section: Intracellular Ca 2+ Signaling Drives Ecfcs' Angiogenic Activitymentioning
confidence: 99%
“…An increase in intracellular Ca 2+ concentration ([Ca 2+ ] i ) is the most versatile signaling pathway whereby either a subtle or gross change in extracellular microenvironment may instruct endothelial cells and circulating ECFCs to perform a specific task to maintain cardiovascular homeostasis [ 1 , 2 , 5 , 6 , 7 , 8 , 9 ]. Distinct spatiotemporal endothelial Ca 2+ signals tightly regulate different functions such as nitric oxide (NO) release [ 10 , 11 , 12 ] and endothelium-dependent hyperpolarization (EDH) [ 13 ], vascular permeability [ 14 , 15 ] and repair [ 16 , 17 ], platelet aggregation and blood coagulation [ 18 , 19 ], leukocyte/lymphocyte infiltration [ 20 , 21 , 22 , 23 ], neurovascular coupling [ 24 , 25 ], wound healing [ 16 , 17 ], angiogenesis [ 5 , 26 ], and vasculogenesis [ 27 ]. An aberrant, i.e., resulting either from intracellular Ca 2+ overload or by the dismantling of a specific oscillatory Ca 2+ pattern, or insufficient elevation in [Ca 2+ ] i may lead to endothelial dysfunction and therefore severely compromise cardiovascular homeostasis, as reported in atherosclerosis [ 28 ], hypertension [ 29 , 30 ], pulmonary artery hypertension (PAH) [ 31 ], type 2 diabetes [ 8 , 32 , 33 ], aging [ 34 ], inflammatory disorders [ 21 , 22 , 35 , 36 , 37 ], Alzheimer’s disease, and cerebrovascular dysfunction [ 34 , …”
Section: Introductionmentioning
confidence: 99%
“…TRP channels can be activated and modulated by a wide variety of stimuli, including chemical agonists, temperature changes, mechanical stress, osmotic pressure and G-protein coupled receptor activation. They play important roles in multiple physiological processes, including nociception [ 12 , 13 , 14 ], thermosensation [ 15 , 16 ], chemosensation [ 17 ], regulation of the vascular tone and permeability [ 18 , 19 , 20 ], release of neuropeptides [ 21 ] and immune cell mediators [ 22 ], ciliary beating [ 23 , 24 , 25 ], mucus secretion [ 26 , 27 ], and barrier function in the airways and the skin [ 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%